Transition to where and to what? Exploring the experiences of transitions to adulthood for young disabled people. (26th November 2021) - Pearson, Charlotte; Watson, Nick; Gangneux, Justine; Norberg, Ida
ABSTRACT: Transition to adulthood for young disabled people remains a major policy failure across OECD countries. The support available is often inappropriate, fails to meet young peoples' needs and they fall through the cracks, becoming lost in the system. Much of the work on transition takes a narrow approach, focussing on the shift from paediatric to adult services in health and social care. Drawing on interviews with young disabled people, collected as part of an evaluation of a new cash-based transitions fund, we explore transitions for young disabled people in Scotland. Like the wider personalisation agenda, this fund aims to promote autonomy and individual responsibility. We examine and critique this approach and argue that while the emphasis on young people and their families as social entrepreneurs can facilitate transition, it can also act as a barrier by failing to tackle broader structural constraints faced by young disabled people. We argue that whilst it is important to promote individual agency, structural disadvantage and inequality frame the transition process and these also have to be tackled. This is harder, and arguably more expensive, but without it there is a danger that attempts to improve transition for young disabled people will fail.